Innovative artifacts of the unofficial anthroponymicon of Ukrainian politics in the contemporary metamodern discourse - Diukar, Kateryna (The Journal of V. N. Karazin Kharkiv National University. Series “Philology”, 2025)
The article is devoted to the study of current trends in unofficial naming, especially neogenic derivative processes. The author aims to explore innovative artifacts of the unofficial anthroponymicon of Ukrainian politics from the perspective of contemporary metamodern discourse. The focus of attention is on nicknames, in particular, of the occasional creation, of representatives of the top echelon of Ukrainian politics, recorded in the Internet space over the past fifteen years. The author traces the regularities of the implementation of traditional anthroponymic formulas at the present stage, as well as the use of non-usual tools for creating nicknames. It is found that the occasional patterns, which are actively involved in the digital age in the creation of appellative and onomastic innovations, are becoming more complex, acquiring hybrid features. The author points out the reorientation of nomination processes from the object of nomination to the nominator and his pragmatic desire to realize his own linguistic creativity. It is noted that the monopolarity of nominations, in particular in conservative systems such as the anthroponymicon, has been gradually shifting towards polyvectoriality over the past thirty years. Attention is paid to anthroponyms-enantiosemantics, in which the polarized meaning did not develop over time on the basis of the characteristics of the secondary object of nomination, in relation to the same object of nomination. It is noted that the attested linguistic artifacts clearly do not fit into the framework of postmodern discourse. The hypothesis is put forward that the worldview paradigm of the representatives of the Ukrainian-speaking community acquires metamodern features, which leads to the creation of contrasting and oscillating onymes. It is pointed out that the pendulum principle becomes dominant in the metamodern discourse in general and its linguistic markers, when polar phenomena are not an element of binarity, but an oscillatory movement between different aspects of life.